Features of agricultural ecological-geological systems of Belarus - Korolev V. A.; Galkin A. N. (Vestnik MGTU)
Natural-technical agricultural ecological-geological systems occupy significant areas in Belarus, but there is only scattered information about their abiotic and biotic components. Based on the classification of ecological-geological systems of the republic developed by the authors, a general description has been compiled and features of abiotic (lithotope, hydrotope, edaphotope) and biotic (microbocenosis, phytocenosis, zoocenosis) components of agricultural EGS are identified. These EGS are characterized by a specific structure and include technogenically transformed components. Most of the agricultural lands of Belarus are located on flat river terraces and flat watersheds, but their plowing gradually led to the formation of a transformed relief. Natural geodynamic processes are practically absent in these territories, but parageneses of engineering-geological processes caused by agricultural activity are developing. The use of fertilizers, herbicides and pesticides transforms natural geochemical fields and changes the properties of natural geochemical barriers. The transformations are caused by changes in albedo on agricultural lands, which causes changes in the radiation-thermal balance of the territories. Soils are transformed into technoedaphotopes, microbiocenoses – into technomicrobiocenoses, phytocenoses – into crop-cenoses, zoocenoses – into technozoocenoses. Natural-technical agricultural ecological-geological systems of Belarus are complex specific formations with characteristic features. It must be taken into account when analyzing ecosystems formed under conditions of heterogeneity of the composition and properties of the technogenic component, as well as during their systematization and ecological-geological surveys.